Faktor-Faktor yang Berpengaruh terhadap Kinerja Lingkungan Perusahaan di Indonesia - Lindrianasari Lindrianasari (Jurnal Akuntansi dan Bisnis, 2008)
This study provides an analysis of the relationship among financial performance and environmental performance. Based on the argument that management’s strategy in financial performance affects each of corporate responsibility, we assume that environmental performance is positively and significantly associated with financial performance. By using four independent variables as proxy financial performance (size, profitability, foreign ownership and export) we found that size is positively and significantly associated with environmental performance. And overall we concluded from 32 companies in Indonesian that relation between environmental performance and financial performance is contradictory theoretical support. This prior empirical research has failed to clarify relationship between the variables.